Pelatihan Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas pada UMK Poklahsar Kembung Rebus - Tina Novianti Sitanggang; Riadi Riadi; Ronald Hasudungan Rajagukguk; Jhon Lismart Benget. P; Annisa Nauli Sinaga (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The purpose of this service is to find out how far UMK Poklahsar Kembung Rebus applies the cash receipts and disbursement accounting information system in its transactions. The method used is library research and field research. Collecting data directly to the field using data collection techniques, namely interviews and observations directly to the owner of the UMK Poklahsar Kembung Rebus. In this service, the PKM Team found that UMK Poklahsar Kembung Rebus had not implemented the cash receipts and disbursements accounting information system properly. The transactions are recorded simply by recording receipts and expenses without applying the applicable accounting information system, so that the financial statements of the UMK Poklahsar Kembung Rebus are also not presented in accordance with PSAK.